DEVELOPMENT OF PRESS TRUST OF INDIA FROM PRINT TO DIGITAL AGE: HISTORICAL PERSPECTIVE - Rai, Dhirendra Kumar; Jaiswal, Harshit Shyam (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Press Trust of India (PTI) is the largest news agency of India. This news agency, which has been a companion of independent India, has a history linked to the history of colonial India and the Indian freedom struggle. This agency has its own importance due to its large network in a vast country like India. Despite the continuous changes in information technology and news gathering, how this news agency has kept itself relevant from the print age to the digital age is a subject worth knowing. Apart from technology, many challenges have come in front of news agencies in India from its inception till the present time. We will try to understand how PTI overcame those challenges through this research article.